2005
DOI: 10.1128/aem.71.10.6228-6234.2005
|View full text |Cite
|
Sign up to set email alerts
|

Survival or Growth of Escherichia coli O157:H7 in a Model System of Fresh Meat Decontamination Runoff Waste Fluids and Its Resistance to Subsequent Lactic Acid Stress

Abstract: A potential may exist for survival of and resistance development by Escherichia coli O157:H7 in environmental niches of meat plants applying carcass decontamination interventions. This study evaluated (i) survival or growth of acid-adapted and nonadapted E. coli O157:H7 strain ATCC 43895 in acetic acid (pH 3.6 ؎ 0.1) or in water (pH 7.2 ؎ 0.2) fresh beef decontamination runoff fluids (washings) stored at 4, 10, 15, or 25°C and (ii) resistance of cells recovered from the washings after 2 or 7 days of storage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Studies have shown that acid application can reduce the populations of aerobic bacteria, fecal coliforms, and E. coli (16). However, the efficacy of such methods has been in doubt since the recognition of acid-tolerant E. coli 0157:H7 (4,15,21,24). Our pure culture studies found that the bactericidal effects of 3% lactic acid for the inactivation of different STEC isolates were variable, with reduction ranging from 0.3 to 3.0 log CFU/ml within 2 min at 21°C.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Studies have shown that acid application can reduce the populations of aerobic bacteria, fecal coliforms, and E. coli (16). However, the efficacy of such methods has been in doubt since the recognition of acid-tolerant E. coli 0157:H7 (4,15,21,24). Our pure culture studies found that the bactericidal effects of 3% lactic acid for the inactivation of different STEC isolates were variable, with reduction ranging from 0.3 to 3.0 log CFU/ml within 2 min at 21°C.…”
Section: Discussionmentioning
confidence: 94%
“…Second, immersing beef in the treatment solution followed by rubbing (hand massaging) was more effective than immersion only, and immersion only was better than a surface spray application for reducing STEC on beef surfaces. Third, STEC may survive in acid-based treatment solutions, and acid-tolerant STEC may recover in the treatment solution following application (24). However, STEC does not survive in levulinic acid plus SDS solution, thereby mitigating the possibility of STEC contamination in fluid remaining after treatment application.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The surface pH of samples was measured by using flat probe pH meter (Prescisa, Switzerland) on 0, 2nd, 6th and 12th days of storage. At this step, each piece of meat (10 g) was aseptically blended with 90 mL of sterile peptone water (Merck, Germany) in a laboratory blender [15] . After that, 1 mL of the blended sample of each inoculated meat with S. aureus was transferred onto Petri dishes for pour plate culturing with standard plate count agar (Merck, Germany) individually.…”
Section: Methodsmentioning
confidence: 99%